The Combination of Dolomite and Hydrated Lime with Different Compositions in Sulfuric Acid Soil for Fish Culture Ponds - Mirna Fitrani; Idsariya Wudtisin; Methee Kaewnern (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research Sulfuric acid soil causes extreme acidity of the water (pH<3) and is unsuitable for fish culture Well management for sulfuric acid soil reduce the high risk of soil and water acidity The use of an appropriate combination of different liming is better than the single material to solve the very low pH Combination of dolomite and hydrated lime increased the pH and alkalinity   Abstract The application of liming material should consider the amount and quality of chemicals related to cost expenditure and target of expected soil properties since it is usually done with an incorrect number's estimation and expected soil-water quality which produces unsuccessful results. This study aimed to analyze the effect of different percentages from each combination of dolomite and hydrated lime (DH); DH1 (75:25), DH2 (50:50), and DH3 (25:75), which used five replications to the soil and water quality. The soil samples were taken from the earthen pond of semi-intensive tilapia fish (Oreochromis niloticus) culture in Lat Bua Luang, Rangsit, Thailand, placed into 50 plastic pots (volume = 1.5 L), and mixed with lime of different compositions. Based on the results, the mixture of dolomite and hydrated lime (DH) increased the soil and water pH into the desirable ranges (7.4-8.6). The alkalinity of DH treatments was not higher than that of the single dolomite (DA) or hydrated lime (HA). However, the value was still sufficient (>75 mg/L as CaCO3) to buffer water quality changes. Several depletions of the toxic materials (total aluminum, iron, and manganese) caused by sulfuric acid (FeS2) had been observed in combination treatment, especially in DH1. On the contrary, the essential base cations, calcium, and magnesium increased beyond the single treatment, either dolomite (DA) or hydrated lime (HA). A combination of dolomite and hydrated lime (DH1) as an alternative treatment to remedy aquaculture ponds in acid-containing soil is suggested in terms of efficiency and possible cost-effectiveness.